Introduction to the special section on drivers with ASD - Volkmar, Fred (Journal of Autism and Developmental Disorders, 2025)
Keywords: Autism; Clinical psychology; Computer science; Developmental psychology; Engineering; Engineering physics; Medicine; Psychology; Public health; Section (typography); Special section; dept.sed

Autism and Pervasive Developmental Disorders - Volkmar, Fred R. (Cambridge University Press, 2019)
Interest in autism and related disorders has exploded. Established as an essential book on this complex syndrome, the new edition has been extensively revised to reflect significant advances in research. Featuring contributions from leading international authorities in the clinical and social sciences, the book covers recent progress in our understanding of the field and offers a perspective on the present state of the discipline. With new material on topics such as evidence-based treatment and practice, the book covers changes in diagnosis resulting from the publication of DSM-V, and developments in how autism is understood, including the removal of language delay as a necessary diagnostic criterion. Far-reaching, the book considers aspects from epidemiology, genetics, and neurobiology, to core symptoms, early interventions, and pharmacology. One section critically surveys the history of autism as a diagnostic concept, and issues such as an ageing population and the impact of research on national policy are considered.
Keywords: dept.sed

Reading comprehension strategies in autism spectrum disorders - Bean, Kimberly (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

Relationship enhancement methods - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Interpersonal supports - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Brainstem Audiometry - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Cochlea - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deafness - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Dichotic Listening - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Hearing - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Otitis Media - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Pediatric Speech Intelligibility Test - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Screening Test for Auditory Processing Disorders - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pits.22757
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race

Evidence-based practices in autism: where we started to where we are now - Reichow, Brian; Doehring, Peter; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Developmental psychology; Psychology; dept.sed

Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, Fred; Doehring, Peter; Reichow, Brian (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Autism spectrum disorder; Cognitive psychology; Developmental psychology; Physics; Psychology; Spectrum (functional analysis); dept.sed

Autism: Social communication disorder - Jackson, Scott Luther James (Encyclopedia of Autism Spectrum Disorders, 2017)
Keywords: dept.aa

Autism spectrum disorder in adolescents and adults: an introduction - Volkmar, Fred R.; Reichow, Brian; McPartland, James C. (Adolescents and Adults with Autism Spectrum Disorders, 2024)
Leo Kanner’s classic description of autism appeared eight decades ago. Although the pace of research has increased dramatically, research specifically focused on adolescents and adults remains limited in many respects. Numerous outcome studies have been conducted and suggest potential for markedly improved outcome with intervention. Unfortunately, studies on adults after early adulthood are sparse and, for old age, almost nonexistent, reflecting a lack of support for research in this population. This is in stark contrast to other developmental disorders in which considerable information on adult life is often available. This book summarizes work across areas, focusing on what is known and not yet known, highlighting important areas for future research. While overall outcome has improved, a small group of individuals remain in need of high levels of adult care. For all individuals, the field requires new approaches to both research and clinical service.
Keywords: Adolescents; Adults; Autism; Outcome; Supports; dept.sed

The need for caregiver support for families of children with ASD - Bean, Kimberly; Meers, K (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.sed

Peer mentors for students with ASD on college campuses - Cook, Barbara; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Differentiating ASD from DLD in toddlers - Paul, Rhea; Chawarska, Katyrzyna; Volkmar, Fred R (Perspectives on Language Learning and Education, 2008)
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-582-369-786-82X tex.type: [object Object]
Keywords: dept.cmd

Deaf-Blind - McCullagh, Jennifer; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

An Introduction to Autism and the Autism Spectrum - Volkmar, Fred R.; Jackson, Scott; Pete, Brian (Handbook of Autism Spectrum Disorder and the Law, 2021)
The syndrome of infantile autism was identified in 1943 (although cases clearly were present earlier). Very quickly there began to be a debate about the nature of autism and the boundaries of the autism phenotype. In the 1970s multiple lines of evidence emerged to suggest that autism should be recognized as a disorder in its own right and this happened in 1980. Since that time there has been an explosion of research and the debate about the boundaries of the diagnostic concept has continued. It does appear that individuals on the autism spectrum present special issues and challenges in terms of their interactions with the legal system at all levels. In this chapter we summarize the state of scientific knowledge and highlight some important areas relevant to those who deal with individuals with autism in legal settings.
Keywords: Asperger’s; Autism; Autism spectrum disorder; Diagnosis; dept.adm

The Diagnosis of Autism: From Kanner to DSM-III to DSM-5 and Beyond - Rosen, Nicole E.; Lord, Catherine; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2021)
In this paper we review the impact of DSM-III and its successors on the field of autism—both in terms of clinical work and research. We summarize the events leading up to the inclusion of autism as a “new” official diagnostic category in DSM-III, the subsequent revisions of the DSM, and the impact of the official recognition of autism on research. We discuss the uses of categorical vs. dimensional approaches and the continuing tensions around broad vs. narrow views of autism. We also note some areas of current controversy and directions for the future.
Keywords: Article; Asperger syndrome; Autism; Autism Spectrum Disorder; Autistic Disorder; Categorical; DSM; DSM-5; DSM-III; DSM-IV; Diagnostic and Statistical Manual of Mental Disorders; Dimensional; History; Humans; ICD-10; ICD-11; Psychology; Recognition; autism; clinical feature; clinical research; cognition; cultural factor; dept.sed; dept.swk; developing country; echolalia; ethnic group; human; language ability; medical history; peer-reviewed; pervasive developmental disorder not otherwise specified; psychiatric diagnosis; psychological aspect; race; sex difference; social class; symptom; tension

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
49 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Language outcomes of toddlers with autism spectrum disorders: A two year follow-up - Paul, Rhea; Chawarska, Katarzyna; Cicchetti, Domenic; Volkmar, Fred (Autism Research, 2008)
Thirty-seven children 15-25 months of age received clinical diagnoses of autism spectrum disorder (ASD) and were re-evaluated two years later. All subjects were judged to have retained a diagnosis of ASD at the follow-up evaluation. Communication scores for the group as a whole during the first visit were significantly lower than nonverbal IQ. However, by the second visit, verbal and nonverbal scores were no longer significantly different. The group was divided into two subgroups, based on expressive language (EL) outcome at the second visit. The two groups were similar in the second year of life in terms of expressive communication skills and autistic symptoms, except for a trend toward more stereotypic and repetitive behavior in the worse outcome group. By the second visit, however, the groups differed significantly on all standard measures of expression and reception, as well as on autistic symptomotology and nonverbal IQ. When assessed during their second year, children who ended up in the better outcome group showed higher average nonverbal cognitive level, receptive language (RL) scores, number of sounds and words produced, use of symbolic play schemes, and response to joint attention bids. Regression analysis revealed that the variables for which significant differences between the two outcome groups in their second year of life were found provided significant prediction of EL outcome at age four. Stepwise regression identified RL and presence of stereotypic and repetitive at the first visit as significantly associated with EL outcome. Implications of these findings for early identification and intervention are discussed.
90 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000270031600004
Keywords: Autism; Autistic Disorder; Child; Preschool; Communication; Follow-Up Studies; Humans; Infant; Language; Language Disorders; Language Tests; Language Therapy; Observer Variation; Questionnaires; Severity of Illness Index; Toddlers; article; autism; dept.cmd; follow up; hospitalization; human; infant; interpersonal communication; language disability; language test; observer variation; preschool child; questionnaire; speech therapy

Autism spectrum disorder in the second year: stability and change in syndrome expression - Chawarska, Katarzyna; Klin, Ami; Paul, Rhea; Volkmar, Fred (Journal of Child Psychology and Psychiatry, 2007)
Objectives: Increasing numbers of young children referred for a differential diagnosis of autism spectrum disorders (ASD) necessitates better understanding of the early syndrome expression and the utility of the existing state-of-the art diagnostic methods in this population. Method: Out of 31 infants under the age of 2 years referred for a differential diagnosis, 19 were diagnosed with autism, and 9 with pervasive developmental disorder-not otherwise specified (PDD- NOS) when reassessed at 3 years. We examined 1) the symptoms of ASD in the second year and changes in the syndrome expression by the age of three; 2) relationship between expert-assigned clinical diagnosis and diagnostic classification based on Autism Diagnostic Observation Schedule-Generic (ADOS-G) and Autism Diagnostic Interview-Revised (ADI-R) in the second year; 3) the relationship between direct observation and parental report of ASD symptoms. Results: Symptoms of autism and PDD- NOS in the second year were pronounced and stability of the clinical diagnosis was high. The agreement between clinician-assigned autism but not PDD- NOS diagnosis and the ADOS-G was high. However, sensitivity of the ADI-R diagnostic classification of autism was poor. Comparison of concurrent parental report and direct observation revealed discrepancies in severity ratings of key dyadic social behaviors. Changes in communication reflected acquisition of language accompanied by the emergence of unusual language characteristics. Symptoms of social dysfunction were relatively stable over time, and so was the severity of stereotyped behaviors. Conclusions: The study provides support for stability of clinical diagnosis and syndrome expression in the second year and highlights advantages and limitations of the ADI-R and ADOS-G for diagnosing and documenting symptoms of ASD in infants.
245 citations (Crossref) [2023-10-31] START/CPEA Network Meeting, Washington, DC, 2004 Citation Key Alias: lens.org/007-431-320-363-097 tex.unique-id: [object Object]
Keywords: ADI-R; ADOS-G; ASD; Assessment; Autism; Autistic Disorder; Child; Preschool; Communication; Diagnosis; Differential; Disease Progression; Early Diagnosis; Earlydiagnosis; Female; Humans; Infant; Infants; Interpersonal Relations; Language Development Disorders; Longitudinal studies; Male; PDD-NOS; Questionnaires; Social Behavior; Stereotyped Behavior; Toddlers; article; assessment; autism; communication disorder; controlled study; dept.cmd; differential diagnosis; disease severity; early diagnosis; female; follow up; human; infants; language disability; longitudinal studies; longitudinal study; male; observational study; patient referral; pervasive developmental disorder not otherwise specified; play; preschool child; psychologic assessment; psychological rating scale; sensitivity analysis; social behavior; social disability; social interaction; stereotypy; symptomatology; toddlers

Conversational Behaviors in Youth with High-functioning ASD and Asperger Syndrome. - Paul, Rhea; Orlovski, Stephanie; Marcinko, Hillary; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2009)
Twenty-nine youth with autism spectrum disorders and 26 with typical development between 12 and 18 years of age were engaged in structured interviews (ADOS). The interviews were videotaped and rated for atypical conversational behaviors by trained raters, using the Pragmatic Rating Scale (Landa et al. Psychol Med 22:245-254, 1992). The ASD group was divided into AS and HFA/PDD-NOS subgroups. Significant differences were found among groups on approximately one-third of the PRS items. These items involved primarily the management of topics and information, reciprocity, intonation, and gaze management. The only differences to reach significance between the AS and HFA/PDD-NOS group were a greater tendency for overly formal speech on the part of the AS group, and more difficulty with gaze management on the part of the group with HFA/PDD-NOS. The implications of these findings for understanding and treating conversational deficits in ASD are discussed., (C) Plenum Publishing Corporation 2009. All Rights Reserved.
173 citations (Crossref) [2023-10-31] Place: (C) Plenum Publishing Corporation 2009. All Rights Reserved.
Keywords: *Asperger Syndrome/di [Diagnosis]; *Autistic Disorder/di [Diagnosis]; *Interpersonal Relations; *Verbal Behavior; Adolescent; Asperger Syndrome; Asperger Syndrome/px [Psychology]; Asperger syndrome; Autism; Autistic Disorder; Autistic Disorder/px [Psychology]; Child; Conversation; Female; Humans; Intelligence; Interpersonal Relations; Keywords; Language Development Disorders; Language Development Disorders/di [Diagnosis]; Language Development Disorders/px [Psychology]; Male; Pragmatics; Pragmatics Conversation; Speech Acoustics; Speech Intelligibility; Verbal Behavior; Vocabulary; article; autism; behavior; clinical article; controlled study; conversation; dept.cmd; human; juvenile; peer-reviewed; priority journal; rating scale; structured interview; videotape

Seeing the forest and the trees: Disentangling autism phenotypes in the age of DSM-5 - Volkmar, Fred R.; Woodbury-Smith, Marc; Øien, Roald A. (Development and Psychopathology, 2021)
This paper, written in honor of Professor Ed Zigler, focuses on some of the themes in developmental disabilities research that were so central to his work. It has now been nearly 80 years since Leo Kanner first identified the prototypic form – early infantile autism – of what is now autism spectrum disorder. In this article we summarize the development of the concept and the important accumulation of knowledge over time that has now led us to the recognition of a broader autism phenotype just as, at the same time, the current official diagnostic system in the USA has narrowed the concept. We also address current controversies regarding autism as the diagnosis is impacted by age and developmental factors, gender, and cultural issues. In parallel to the work on intellectual deficiency and development pioneered by Zigler and his colleagues, we summarize some of the challenges for the years ahead.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102496361
Keywords: Autism Spectrum Disorder; Autistic Disorder; Diagnostic and Statistical Manual of Mental Disorders; Humans; Phenotype; Psychology; Recognition; autism; dept.sed; human; peer-reviewed; phenotype

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Perception and Production of Prosody by Speakers with Autism Spectrum Disorders. - Paul, Rhea; Augustyn, Amy; Klin, Ami; Volkmar, Fred R (Journal of Autism and Developmental Disorders, 2005)
Speakers with autism spectrum disorders (ASD) show difficulties in suprasegmental aspects of speech production, or prosody, those aspects of speech that accompany words and sentences and create what is commonly called "tone of voice." However, little is known about the perception of prosody, or about the specific aspects of prosodic production that result in the perception of "oddness." The present study examined the perception and production of a range of specific prosodic elements in an experimental protocol involving natural speech among speakers with ASD between 14 and 21 years of age, in comparison with a typical control group. Results revealed ceiling effects limiting interpretation of findings for some aspects of prosody. However, there were significant between-group differences in aspects of stress perception and production. The implications of these findings for understanding prosodic deficits is speakers with autism spectrum disorders, and for future research in this area, are discussed.
257 citations (Crossref) [2023-10-31] Place: United States Paul, Rhea. Southern Connecticut State University, USA. rhea.paul@yale.edu
Keywords: *Autistic Disorder/co [Complications]; *Language Disorders/et [Etiology]; *Perceptual Disorders/et [Etiology]; *Phonetics; *Speech Disorders/et [Etiology]; *Speech Perception; Adolescent; Adult; Autism; Autistic Disorder; Humans; Language; Language Disorders; Language Disorders/di [Diagnosis]; Language Tests; Male; Perceptual Disorders; Perceptual Disorders/di [Diagnosis]; Phonetics; Prosody; Speech Discrimination Tests; Speech Disorders; Speech Disorders/di [Diagnosis]; Speech Perception; Speech Production Measurement; article; autism; child; clinical article; clinical protocol; controlled study; correlation analysis; dept.cmd; human; intelligence quotient; intermethod comparison; language; medical assessment; peer-reviewed; perception; priority journal; prosody; reliability; scoring system; speech; speech disorder; statistical significance; stress; task performance

Core dimensions of autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L.J. (New Oxford Textbook of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests during the early developmental period of childhood. Behaviourally characterized by impairments in social interaction and communication, in combination with stereotyped and restricted patterns of behaviour and/or interest, it is currently believed that ASD occurs in approximately 1–2% of individuals. ASD is more prevalent among males than females (4–5:1), but the mechanisms resulting in this discrepancy are still unclear. This chapter will serve as an introduction to ASD, covering the topics of disorder history, prevalence rates, demographics, diagnostic criteria, differential diagnosis, and discussions on current and future diagnostic classification systems. The remaining chapters within Section 4 will then provide detailed discussions on more specific topics related to ASD, including current understandings of treatment planning, prevention and epidemiology, genetics, imaging, and disorder management.
tex.ids: volkmarCoreDimensionsAutism2020a
Keywords: dept.sed

“Listen my children and you shall hear”: Auditory preferences in toddlers with autism spectrum disorders - Paul, Rhea; Chawarska, Katarzyna; Fowler, Carol; Cicchetti, Domenic; Volkmar, Fred (Journal of Speech Language and Hearing Research, 2007)
Purpose: This study tests the hypothesis that toddlers with autism spectrum disorders (ASD) will show differences from contrast groups in preferences for attending to speech. Method: This study examined auditory preferences in toddlers with ASD and matched groups of (a) typical age-mates, (b) age-mates with nonautistic developmental disabilities, and (c) younger children matched for language age. The experimental procedure measured time spent oriented to auditory stimuli that were created to exemplify language patterns that had been studied in typically developing infants. Results: Findings suggest that toddlers with ASD show a reduced preference for child-directed speech, compared with typical age-mates, but few differences from children with nonautistic developmental disorders. Correlational analysis revealed that time spent listening to child-directed speech by children with ASD was related to their concurrent receptive language ability as well as to receptive language abilities 1 year later. This relationship did not hold for the other groups. Conclusion: The present study supports the hypothesis that children with ASD perform differently from typical peers in auditory preference paradigms and that performance in these tasks is related to concurrent and later language development.
75 citations (Crossref) [2023-10-31] tex.eissn: 1558-9102 tex.unique-id: ISI:000250280300017
Keywords: *Attention; *Autistic Disorder/px [Psychology]; *Child Behavior; *Choice Behavior; *Infant Behavior; *Speech Perception; Attention; Auditory comprehension; Autism spectrum disorders; Autistic Disorder; Child Behavior; Child; Preschool; Choice Behavior; Comprehension; Female; Humans; Infant; Infant Behavior; Language Development; Language comprehension; Male; Speech Perception; article; auditory stimulation; auditory system; autism; controlled study; correlation analysis; dept.cmd; developmental disorder; female; human; language; language ability; language development; major clinical study; male; peer group; preschool child; speech; time; toddler

Vulnerability to Ideologically-Motivated Violence Among Individuals With Autism Spectrum Disorder - Woodbury-Smith, Marc R.; Loftin, Rachel; Westphal, Alexander; Volkmar, Fred R. (Frontiers in Psychiatry, 2022)
People with autism spectrum disorder (ASD) are represented among those who espouse extremist thought and have committed violent acts associated with their beliefs. Media often highlight a perpetrator's psychiatric diagnosis following acts of mass violence, which in some instances has included ASD. ASD may itself not provide useful information for understanding motivations. Instead, understanding specific traits and neuropsychological and other vulnerabilities may offer an opportunity to make sense of these very complex events.
2 citations (Crossref) [2023-10-31]
Keywords: dept.sed; peer-reviewed

Considering emerging, complementary, and alternative treatments - Øien, Roald; Nordahl‐Hansen, Anders; Skarbek, Sacha; Tolkin, Samuel; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Computer science; dept.sed

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
104 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.sed

Babysitter training guide for families with individuals with ASD - Bean, K; Neers, K; Cook, Barbara; Eren, R (Encyclopedia of Autism Spectrum Disorders, 2020)
The Second Edition of this major reference work expands its coverage and continues to break new ground as an electronic resource for students, educators, researchers, and professionals. Comprehensive in breath and textbook in depth, the Second Edition of the Encyclopedia of Autism Spectrum Disorders serves as a reference repository of knowledge in the field as well as a regularly updated conduit of new knowledge long before such information trickles down from research to standard textbooks. The Second Edition of the Encyclopedia digests and presents new and updated information for readers who need to stay current with the latest research and clinical practices, including advances in neurobiology and genetics, diagnostic instruments and assessment tests, pharmaceutical treatments, and behavioral, speech and language, and other rehabilitative therapies. The Second Edition of the Encyclopedia covers topics across the following major conceptual areas of ASD and PDDs, including: Research trends and findings Behavior/speech Communication TreatmentsEducation Taking advantage of the techniques offered by the electronic medium, the Second Edition of the Encyclopedia of Autism Spectrum Disorders offers an extensive cross-referencing system facilitating search and retrieval of information. This unique, comprehensive Second Edition of the Encyclopedia of Autism Spectrum Disorders is an essential reference for advanced undergraduate and graduate students as well as researchers, professors, clinicians, and other practitioners across such related disciplines as developmental psychology, child and adolescent psychiatry, social work, child and school psychology, behavioral therapy, and sociology of education.
Keywords: dept.cmd

Production of syllable stress in speakers with autism spectrum disorders - Paul, Rhea; Bianchi, Nancy; Augustyn, Amy; Klin, Ami; Volkmar, Fred R. (Research in Autism Spectrum Disorders, 2008)
This paper reports a study of the ability to reproduce stress in a nonsense syllable imitation task by adolescent speakers with autism spectrum disorders (ASD), as compared to typically developing (TD) age-mates. Results are reported for both raters' judgments of the subjects' stress production, as well as acoustic measures of pitch range and duration during stressed and unstressed syllable production. Results reveal small but significant differences between speakers with ASD and typical speakers in both perceptual ratings of stress and instrumental measures of duration of syllables. The implications of these findings for understanding prosodic deficits in ASD are discussed. (C) 2007 Elsevier Ltd. All fights reserved.
47 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/160-980-016-423-349 tex.unique-id: [object Object]
Keywords: Autism; Prosody; Syllable stress; acoustics; adolescent; adult; article; autism; clinical article; controlled study; dept.cmd; feedback system; female; human; intelligence quotient; male; mental task; motor coordination; pitch; priority journal; school child; speech articulation; speech perception; task performance

Brief Report: Bullying and Anxiety in High-Functioning Adolescents with ASD - van Schalkwyk, Gerrit; Smith, Isaac C.; Silverman, Wendy K.; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Youth with ASD are more likely to experience bullying than their typically developing peers. This risk has not been studied in youth with ASD transitioning to college. We examined the occurrence of bullying in 35 high functioning youth with ASD who were preparing to attend college. We also examined youth anxiety and ASD symptoms. Fifty-one percent of the sample reported being recent victims of bullying; 31% of parents reported their child was a victim of bullying. Parent report of bullying correlated significantly with ratings of youth social anxiety symptoms. These findings suggest that bullying is an issue of concern for higher functioning, older adolescents with ASD, and that their own reports may be particularly important in identifying its occurrence.
Keywords: Anxiety; Autism spectrum disorder; Bullying; Postsecondary education; dept.sed

Brief Report: Relations between Prosodic Performance and Communication and Socialization Ratings in High Functioning Speakers with Autism Spectrum Disorders. - Paul, Rhea; Shriberg, Lawrence; McSweeny, Jane; Cicchetti, Domenic; Klin, Ami; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2005)
Shriberg et al. [ Shriberg, L. et al. (2001). Journal of Speech, Language and Hearing Research, 44, 1097-1115] described prosody-voice features of 30 high functioning speakers with autistic spectrum disorder (ASD) compared to age-matched control speakers. The present study reports additional information on the speakers with ASD, including associations among prosody-voice variables and ratings of communication social abilities. Results suggest that the inappropriate sentential stress and hypernasality previously identified in some of these speakers is related to communication/sociability ratings. These findings and associated trends are interpreted to indicate important links between prosodic performance and social and communicative competence. They suggest the need for careful assessment of inappropriate prosody and voice features in speakers with ASD, and for effective intervention programs aimed at reducing the stigmatization of individuals with these conditions., (C) Plenum Publishing Corporation 2005. All Rights Reserved.
131 citations (Crossref) [2023-10-31] Place: (C) Plenum Publishing Corporation 2005. All Rights Reserved.
Keywords: Adolescent; Adult; Asperger syndrome; Autism; Autistic Disorder; Communication; Female; Humans; Male; Middle Aged; Prosody; Severity of Illness Index; Socialization; Speech; Speech Production Measurement; Voice Quality; adolescent; adult; article; autism; child; clinical article; communication; communication skill; controlled study; dept.cmd; female; hospitalization; human; human experiment; interpersonal communication; linguistics; male; middle aged; nasal speech; peer-reviewed; priority journal; prosody; social adaptation; social psychology; socialization; speech; speech analysis; speech disorder; verbal communication; voice

Parental recognition of developmental problems in toddlers with autism spectrum disorders - Chawarska, Katarzyna; Paul, Rhea; Klin, Ami; Hannigen, Sarah; Dichtel, Laura E.; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2007)
Symptoms of Autism Spectrum Disorders (ASD) begin to manifest during the first 2 years; there is limited evidence regarding type and timing of symptom onset. We examined factors related to parental age of recognition (AOR) of early abnormalities and the association between AOR and diagnosis and levels of functioning at 2 and 4 years in 75 toddlers with ASD. Results suggest significant differences between autism and PDD-NOS in the AOR and type of first concerns. Early social and motor delays as well as maternal age was associated with AOR. Later AOR was associated with poorer social-communicative and nonverbal cognitive functioning at 2 and 4. The findings are discussed in a context of identifying distinct developmental trajectories within the autism spectrum.
175 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-540-720-732-679 tex.unique-id: [object Object]
Keywords: Age Factors; Age of recognition; Autism; Autistic Disorder; Child; Preschool; Cognition Disorders; Developmental Disabilities; Early Diagnosis; Female; Follow-Up Studies; Humans; Infants; Male; Mass Screening; PDD-NOS; Parents; Recognition (Psychology); Regression; Severity of Illness Index; Social Behavior; article; autism; clinical feature; dept.cmd; developmental disorder; early diagnosis; functional assessment; human; major clinical study; maternal age; motor performance; nonverbal communication; parental attitude; peer-reviewed; preschool child; priority journal; social interaction

Practicing Evidence-Based Practices - Eren, Ruth Blennerhassett; Brucker, Pamela Owen (Evidence-Based Practices and Treatments for Children with Autism, 2011)
Public education in the United States has a history of local control in the development of curriculum and instruction. Although notable court decisions have led to more universal applications of educational policy and practices (Brown v. Board of Education 1954, Oberti v. Clementon 1993), it has been federal law that has resulted in significant changes in instruction. The Individuals with Disabilities Education Improvement Act (IDEA; Public Law 108–142), first enacted in Public Law 94–142, guaranteed the right of a free, appropriate public education for all children, regardless of the severity of their disability. The word “appropriate” resulted in the beginning of what we refer to today as differentiated instruction: instructional strategies that allow a child to learn and progress in an educational setting. The federal law, No Child Left Behind (NCLB; Public Law 107-110), enacted in 2001, contributed to this initiative and added a caveat that these differentiated instructional strategies needed to be grounded in scientifically based research. Indeed, the term “scientifically based research” has been noted to appear in NCLB 111 times (Deshler 2002). The federal government, in IDEA 2004, identified 13 eligibility categories. In order to receive special education services, a student must, through a multidisciplinary evaluation, meet the eligibility criteria established for one of the 13 categories. Since 1975, when PL94–142 was enacted, educational interventions for students receiving special education have expanded, particularly in disability categories with a high level of incidence such as speech and language disorders and learning disabilities. Low-incidence disabilities, such as mental retardation, visual impairments, and autism, have received less attention.
Citation Key Alias: lens.org/104-519-704-094-108
Keywords: General Education; Individualize Education Program; Special Education; Special Education Teacher; Team Meeting; dept.sed

Speech and prosody characteristics of adolescents and adults with high-functioning autism and asperger syndrome - Shriberg, Lawrence D.; Paul, Rhea; McSweeny, Jane L.; Klin, Ami; Cohen, Donald J.; Volkmar, Fred R. (Journal of Speech Language and Hearing Research, 2001)
Speech and prosody-voice profiles for 15 male speakers with High-Functioning Autism (HFA) and 15 male speakers with Asperger syndrome (AS) were compared to one another and to profiles for 53 typically developing male speakers in the same 10- to 50-years age range. Compared to the typically developing speakers, significantly more participants in both the HFA and AS groups had residual articulation distortion errors, uncodable utterances due to discourse constraints, and utterances coded as inappropriate in the domains of phrasing, stress, and resonance. Speakers with AS were significantly more voluble than speakers with HFA, but otherwise there were few statistically significant differences between the two groups of speakers with pervasive developmental disorders. Discussion focuses on perceptual-motor and social sources of differences in the prosody-voice findings for individuals with Pervasive Developmental Disorders as compared with findings for typical speakers, including comment on the grammatical, pragmatic, and affective aspects of prosody.
362 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.cmd

What are we optimizing for in autism screening? Examination of algorithmic changes in the M-CHAT - Schjølberg, Synnve; Shic, Frederick; Volkmar, Fred R.; Nordahl-Hansen, Anders; Stenberg, Nina; Torske, Tonje; Larsen, Kenneth; Riley, Katherine; Sukhodolsky, Denis G.; Leckman, James F.; Chawarska, Katarzyna; Øien, Roald A. (Autism research : official journal of the International Society for Autism Research, 2021)
The present study objectives were to examine the performance of the new M-CHAT-R algorithm to the original M-CHAT algorithm. The main purpose was to examine if the algorithmic changes increase identification of children later diagnosed with ASD, and to examine if there is a trade-off when changing algorithms. We included 54,463 screened cases from the Norwegian Mother and Child Cohort Study. Children were screened using the 23 items of the M-CHAT at 18 months. Further, the performance of the M-CHAT-R algorithm was compared to the M-CHAT algorithm on the 23-items. In total, 337 individuals were later diagnosed with ASD. Using M-CHAT-R algorithm decreased the number of correctly identified ASD children by 12 compared to M-CHAT, with no children with ASD screening negative on the M-CHAT criteria subsequently screening positive utilizing the M-CHAT-R algorithm. A nonparametric McNemar's test determined a statistically significant difference in identifying ASD utilizing the M-CHAT-R algorithm. The present study examined the application of 20-item MCHAT-R scoring criterion to the 23-item MCHAT. We found that this resulted in decreased sensitivity and increased specificity for identifying children with ASD, which is a trade-off that needs further investigation in terms of cost-effectiveness. However, further research is needed to optimize screening for ASD in the early developmental period to increase identification of false negatives. © 2021 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC.
4 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34837355/
Keywords: Article; Autism Spectrum Disorder; Autistic Disorder; Checklist; Child; Cohort Studies; Female; Humans; Infant; M CHAT R algorithm; M CHAT algorithm; Mass Screening; McNemar test; Mothers; algorithm; autism; checklist; child; cohort analysis; controlled study; cost effectiveness analysis; dept.sed; developmental stage; diagnostic accuracy; diagnostic test accuracy study; early diagnosis; false negative result; female; gold standard; human; infant; major clinical study; mass screening; mother; nonparametric test; peer-reviewed; procedures; process optimization; psychometry; reference value; scoring system; sensitivity and specificity; statistical significance